2020
DOI: 10.3390/ijerph17030849
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Durability of Transfer Training in Fencing

Abstract: This paper reports the results of an experiment that aimed to study transfer training in fencing. Fencers from the experimental group underwent six-week transfer training while those from the control group underwent regular fencing training. The fencers’ performance was analyzed thrice: before the experimental training (pretest), immediately after it (posttest), and four weeks after it (retention test). Using a device that simulates fencing moves and analyzes the accuracy of such performance, participants comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Also, in a study conducted on male fencers, better results in the dominant hand speed movement were observed after six weeks of transfer training of the non-dominant side. The authors also demonstrated that bilateral transfer may be effective in fencing training [25].…”
Section: Discussionmentioning
confidence: 94%
“…Also, in a study conducted on male fencers, better results in the dominant hand speed movement were observed after six weeks of transfer training of the non-dominant side. The authors also demonstrated that bilateral transfer may be effective in fencing training [25].…”
Section: Discussionmentioning
confidence: 94%
“…In the findings of the study, they stated that the handgrip strength of the defenders was 28.4 kg. Witkowski et al, (2020) measured the handgrip strength of male and female athletes (all fencers were right-handed) between the ages of 14-20 in their study. In the findings of the study, they stated that the average handgrip strength of the fencers was 28.08 kg for the right hand and 23.41 kg for the left hand.…”
Section: Discussionmentioning
confidence: 99%
“…Such an approach is focused on intensive cognitive development while stimulating physical development [27]. Nonetheless, it may also contribute-as the effect of an interhemispheric transfer-to increasing the effectiveness of PE in the context of physical parameters, especially in terms of object control skills [81,82]. Perhaps if the control group used Eduball, there would be no deterioration of these competencies, as was the case in the experimental/Eduball group.…”
Section: Eduball and Motor Developmentmentioning
confidence: 99%